The Guardian Weekly : A week in the life of the world : Global Edition - The Guardian Media Group (London : The Guardian Media Group)
The Guardian Weekly magazine is a round-up of the world news, opinion and long reads that have shaped the week. Inside, the past seven days' most memorable stories are reframed with striking photography and insightful companion pieces, all handpicked from the Guardian and the Observer.
Keywords: Actualiteit; Internationaal nieuws; Nieuws